THE EVOLUTION OF DIGITAL THERAPEUTICS (DTx) IN MENTAL HEALTH CARE: A SYSTEMATIC REVIEW OF SOCIAL IMPACT, ETHICAL CHALLENGES, AND PATIENT ENGAGEMENT - Alicja Maria Mitan; Weronika Napierała; Karolina Magda Leszczyńska; Jeremi Leon Jasiński; Anna Krzysztofik; Karolina Krawczyk; Kamila Teresa Kańska; Aleksandra Maria Tomaszewska; Maciej Tomasz Wieczorek; Karolina Julia Hak (International Journal of Innovative Technologies in Social Science, 2026)
Background: The global landscape of mental health care has undergone a fundamental transformation driven by the emergence of Digital Therapeutics (DTx). These software-driven, evidence-based interventions are designed to deliver high-quality psychological support directly to the user. As traditional healthcare infrastructures face unprecedented strain and accessibility crises, DTx has transitioned from a niche supplementary tool to a cornerstone of modern digital psychiatry, redefining how clinical outcomes are achieved and measured in the digital age.Objective: This systematic review critically evaluates the rapid evolution of the DTx sector between 2020 and 2026. The primary objective is to analyze three pivotal dimensions: the broader social implications of digital health democratization, the shifting ethical complexities introduced by the integration of Generative Artificial Intelligence (GenAI), and the persistent socio-technical barriers that hinder long-term patient adherence and therapeutic efficacy.Methodology: Adhering to the PRISMA 2020 guidelines, a comprehensive systematic search was executed across PubMed, Scopus, and Web of Science. The synthesis included twenty-five high-impact studies focused on digital psychiatry, socio-technical frameworks, and algorithmic ethics. The analysis encompassed peer-reviewed literature regarding clinical validation processes, global regulatory shifts (such as the German DiGA market), and the principles of user-centered design (Abbas et al., 2025; Jiang et al., 2025; Gensorowsky et al., 2024).Results: Findings reveal that while DTx offers a viable pathway for expanding care (Carlbring et al., 2018), significant "digital divides" persist. Socioeconomic status and digital literacy remain primary gatekeepers, preventing equitable distribution among marginalized and socioeconomically disadvantaged populations (Divatia et al., 2026; Hengst et al., 2023; Piers et al., 2023). Ethical challenges have evolved from basic data privacy toward sophisticated debates on algorithmic bias, the "black box" nature of AI diagnostics, and the critical necessity for "human-in-the-loop" oversight to mitigate clinical risks (Rahsepar Meadi et al., 2025; Shakeel et al., 2025). Furthermore, patient attrition remains the "Achilles heel" of digital interventions (Nwosu et al., 2022). Sustainable engagement is now increasingly linked to the implementation of "precision engagement" frameworks and the successful cultivation of a digital therapeutic alliance (Eiselt et al., 2025; Smith et al., 2025).Conclusion: The evolution of DTx from 2020 to 2026 necessitates a paradigm shift toward a hybrid socio-technical ecosystem. Future success in the next decade will depend on moving beyond isolated clinical efficacy toward implementation strategies that are radically inclusive, ethically grounded, and designed for deep, human-centric engagement. Addressing the intersection of AI ethics and social equity is no longer optional but a requirement for the next generation of digital mental health care.